Dietary fatty acid intake in hemodialysis patients and associations with circulating fatty acid profiles: a cross-sectional study - Khor, Ban Hock; Sahathevan, Sharmela; Sualeheen, Ayesha; Md Ali, Mohammad Syafiq; Narayanan, Sreelakshmi Sankara; Chinna, Karuthan; Abdul Gafor, Abdul Halim; Goh, Bak Leong; Ahmad, Ghazali; Morad, Zaki; Mat Daud, Zulfitri 'Azuan; Khosla, Pramod; et al. (Oxford University Press, 2019)
Objectives: The aims of this study were threefold: first, to assess the dietary fatty acid (FA) intake and blood FA status in Malaysian patients on hemodialysis (HD); second, to examine the association between dietary FA intakes and blood FA profiles in patients on HD; and third, to determine whether blood FAs could serve as a biomarker of dietary fat intake quality in these patients. Methods: Using 3 d of dietary records, FA intakes of 333 recruited patients were calculated using a food database built from laboratory analyses of commonly consumed Malaysian foods. Plasma triacylglycerol (TG) and erythrocyte FAs were determined by gas chromatography. Results: High dietary saturated fatty acid (SFA) and monounsaturated fatty acid (MUFA) consumption trends were observed. Patients on HD also reported low dietary ω-3 and ω-6 polyunsaturated fatty acid (PUFA) consumptions and low levels of TG and erythrocyte FAs. TG and dietary FAs were significantly associated respective to total PUFA, total ω-6 PUFA, 18:2 ω-6, total ω-3 PUFA, 18:3 ω-3, 22:6 ω-3, and trans 18:2 isomers (P < 0.05). Contrarily, only dietary total ω-3 PUFA and 22:6 ω-3 were significantly associated with erythrocyte FAs (P < 0.01). The highest tertile of fish and shellfish consumption reflected a significantly higher proportion of TG 22:6 ω-3. Dietary SFAs were directly associated with TG and erythrocyte MUFA, whereas dietary PUFAs were not. Conclusion: TG and erythrocyte FAs serve as biomarkers of dietary PUFA intake in patients on HD. Elevation of circulating MUFA may be attributed to inadequate intake of PUFAs.